Implementasi manajemen kelas sosio-emosional pada peserta didik kelas IV-V community learning center (CLC) prolific malaysia - Larasati, Luthfi Dimar; Marmoah, Sri (Universitas Sebelas Maret, 2026)
This study aims to describe the implementation of social-emotional classroom management of fourth and fifth-grade students at the Community Learning Center (CLC) Prolific, located in Sandakan, Malaysia. Employing a descriptive qualitative approach, data were obtained through classroom observations, teacher interviews, and document analysis, and analyzed using the Miles and Huberman interactive model with triangulation techniques to ensure data validity. The findings indicate that the implementation centers on four main aspects: emotional awareness, social relationships, self-resilience and decision making or life experiences, and communication development. Teachers integrated reflective dialogue, collaborative activities, personal storytelling, nonverbal communication training, and participatory conflict resolution as core strategies. These approaches fostered a classroom environment that supports open expression, empathy, and mutual respect, while also strengthening students’ confidence, listening skills, and ability to communicate assertively and critically. The teacher’s role as a model of positive communication was pivotal in shaping a supportive and inclusive classroom culture. The study concludes that socio-emotional classroom management, when implemented consistently, contributes significantly to the development of interpersonal communication skills and can be recommended as a best practice for multicultural and nonformal educational settings. The findings of this study are expected to provide theoretical contributions in the development of socio-emotional-based classroom management as well as practical applications for teachers and educational institutions in creating a learning climate that supports students' social and emotional well-being.